Analysis of Adsorption, Ion Exchange, Thermodynamic Behaviour of Some Organic Cations on Dowex 50WX4-50/H+ Cation Exchanger in Aqueous Solutions - Ehteram A. Noor; Fatma M. Al-Solmi (E-Journal of Chemistry)
The equilibrium adsorption, ion exchange characteristics of various concentrations of some organic cations from aqueous solutions onto dowex 50WEX/H+ cation exchanger were studied at different temperatures in the range of 30-50 °C. The studied cations showed good adsorptive properties onto dowex 50WX4-5/H+ at different concentrations and temperatures. Main adsorption behaviour was ion exchange between hydrogen ions and the organic cations as indicated from the linear relation between the initial concentration of the organic cations and the released hydrogen ions. It was found that the adsorption affinity of dowex 50WX4-50/H+ towards the studied organic cations depends on the substituent type of the organic cations giving the following increasing order: 1-H < 2-OH < 3-OCH3. Thermodynamic parameters for the adsorption of the studied organic cations were evaluated and discussed. It was found that the adsorption 1-H organic cation was spontaneous, ordered, exothermic and favored with decreasing temperature. On the other hand the adsorption of both 2-OH and 3-OCH3 organic cations was found to be spontaneous and disordered with enthalpy change varies significantly with increasing organic cation concentration, suggesting dipole-dipole adsorption forces as new active sites for adsorption under conditions of relatively high concentrations. Freundlich and Dubinin-Radushkevich adsorption isotherm models reasonably describe the adsorption of the studied organic cations onto dowex 50WX4-50/H+ by segmented straight lines depending on the studied range of concentration, indicating the existence of two different sets of adsorption sites with substantial difference in energy of adsorption. According to Dubinin-Radushkevich adsorption isotherm model, physical-ion exchange mechanism was suggested for the adsorption of 1-H organic cation and both physical and chemical-ion exchange mechanisms were suggested for the adsorption of 2-OH and 3-OCH3 organic cations depending on the studied range of concentration.